Ratusz Gł[ówny]. Odbudowa wieży [fot.] Kazimierz Lelewicz. - Lelewicz, Kazimierz (1896-1986) (1951)
Przedstawia fragment środkowego wieńca konstrukcji stalowej wieży Ratusza Głównego Miasta, stan w 1951 r.